Pola Perilaku Harimau Sumatera (Panthera Tigris Sumatrae) di Pusat Rehabilitasi Harimau Sumatera Dharmasraya (PR-HSD) Arsari dalam Kawasan PT. Tidar Kerinci Agung, Sumatera Barat - Muhamad Fadly; Defri Yoza; Viny Volcherina Darlis (HUTAN TROPIKA, 2023)
Phantera tigris sumatrae has a fairly high adaptability to changes in habitat outside its natural habitat, as for changes in areas that have changed functions which were formerly forest areas but are now community gardens, which causes Sumatran tigers to leave and enter community settlements in search of food sources due to forest area shifts. Sumatran tigers can still be found on the island of Sumatra, Lack of public knowledge about Sumatran tiger activities that can endanger livestock and endanger human lives at the same time. Therefore, Sumatran tigers are hunted, captured, and snared. Therefore, information on Sumatran tiger activities is important in an effort to preserve and protect Sumatran tigers. This research method is focal time sampling. This research was conducted from July 2021 to August 2021 for 30 effective days every day to collect daily data on Sumatran tigers. The objects observed in each individual based on sex and age were adult females and juvenile males. Based on the results of the study, it was concluded that the highest daily activity in adult females was moving behavior with a percentage of 21.0%, followed by rest 18.7%, social 1.2%, grooming 1.0%, eating and drinking 0.4%, defecation and urination 0.3%, other activities 57.4%, while for adolescent males the highest activity was moving with a percentage of 12.64%, followed by rest 5.47%, Grooming 0.44%, social 0.37%, eating 0, 30%, other activities 80.32%. Suggestions from this study are the need for further research in order to determine the behavior patterns and adaptations of the Sumatran tiger at the Dharmasraya Sumatran tiger rehabilitation center, West Sumatra.